Measurement of adsorption constants of laccase on gold nanoparticles to evaluate the enhancement in enzyme activity of adsorbed laccase - Peixoto de Almeida, Miguel (2019)
Susana Sousa, Departamento de Doenças Infeciosas, Instituto Nacional de Saúde Doutor Ricardo Jorge, Porto, Portugal